Utilization of morcellation during laparoscopic surgery of uterine fibroid: yes or not? - Balkenzhe Imankulova; Talshyn Ukubassova (Ķazaķstannyṇ Klinikalyķ Medicinasy, 2017)
Objective. The study of the need for a diﬀerentiated approach to morphology during laparoscopic myomectomy and hysterectomy, for the prevention of the spread of an undiagnosed malignant process. Methods. The retrospective analysis 134 operations of a myomektomiya and a hysterectomy which are carried out in National scientifc center of Maternity and the Child Health in 2014 and 2015, where in one case the high-diﬀerentiated adenocarcinoma is noted after a laparotomy aproch total hysterectomy with ovarium and tubs is carried out. Results. Recommendations are given for conducting a total hysterectomy and extraction of the uterus through the vagina and use of endobago during the fermentation of myomatous nodes to prevent the spread of malignant processes. Conclusion. It is advisable to support the recommendations of the American Collegium of Obstetricians and Gynecologists, the European Society for Gynecological Endoscopy and the American Society of Gynecological Laparoscopy on the oncologic alertness of using a morphator during laparoscopic surgery for uterine myomas.